Perfectionism and athlete burnout in junior elite athletes: the mediating role of coping tendencies - Hill, A. P.; Hall, H. K.; Appleton, P. R. (Anxiety, Stress and Coping, 2009)
Recent research indicates that some dimensions of perfectionism are positively related to athlete burnout, whereas others are negatively related to athlete burnout. The divergent relationship between these dimensions of perfectionism and athlete burnout may be explained by different coping tendencies. The present investigation examined whether different coping tendencies mediate the relationship between self-oriented and socially prescribed perfectionism and burnout. Two-hundred and six junior elite athletes (M age=15.15 years, SD=1.88 years, range=11-22 years) completed measures of self-oriented and socially prescribed perfectionism, coping tendencies, and athlete burnout. Structural equation modeling indicated that the relationship between dimensions of perfectionism and athlete burnout was mediated by different coping tendencies. Higher levels of socially prescribed perfectionism was related to higher levels of avoidant coping which, in turn, was related to higher levels of athlete burnout. In contrast, higher levels of self-oriented perfectionism was related to higher levels of problem-focused coping and lower levels of avoidant coping which, in turn, was related to lower levels of athlete burnout. The findings suggest that different coping tendencies may underpin the divergent relationship between self-oriented and socially prescribed dimensions of perfectionism and athlete burnout.